Influence of desensitizing agents on the microshear bond strength of adhesive systems to dentin. - Maeda, Fernando A; Guedes, Ana P A; Catelan, Anderson; Pavan, Sabrina; Briso, André Luiz Fraga [UNESP]; Sundfeld, Renato Herman [UNESP]; Santos, Paulo Henrique dos [UNESP] (My University, 2009)
The aim of this study was to evaluate the effect of desensitizing agents on the micro-shear bond strength of adhesive systems to dentin. Forty bovine teeth were divided into 8 groups (n=5): G1--Single Bond (SB); G2--GH.F + SB; G3-- Desensibilize + SB; G4--essensiv + SB; G5 --ingle Bond 2 (SB2); G6--H.E + SB2; G7--esensibilize + SB2; G8--Dessensiv + SB2. In all of the groups, the desensitizing agents were applied after phosphoric acid etching and before the dentin adhesive application. Z250 composite resin tubes were bonded on the treated surface. After 24 hours, the teeth were tested in a universal machine. Data were submitted to ANOVA and Tukey's test (5%). The results showed that the groups where Desensibilize and Dessensiv were applied exhibited smaller bond strength values.
Keywords: dentin bonding agent; nitrate; potassium derivative; potassium nitrate; resin cement; strontium; strontium chloride; animal; cattle; dental acid etching; dental bonding; dental care; dentin sensitivity; materials testing; shear strength; Acid Etching, Dental; Animals; Cattle; Dental Bonding; Dental Stress Analysis; Dentin Sensitivity; Dentin-Bonding Agents; Materials Testing; Nitrates; Potassium Compounds; Resin Cements; Shear Strength; Strontium